INVESTIGATION ON HOT DEFORMATION BEHAVIOR OF AL-CU-MG-PB ALLOY - Rezaei Ashtiani, hamidreza; shahsavari, p. (Journal of Advanced Manufacturing Technology (JAMT), 2016)
In order to find material parameters of established Zener–Hollomon constitutive equations and predict high-temperature flow stress of Al-Cu-Mg-Pb alloy, isothermal hot compression tests were conducted at constant stain rates of 0.005, 0.05 and 0.5 s-1 and at temperatures ranging from 623 to 773 K at intervals of 50K. The results show that the flow stress of Al-Cu-Mg-Pb alloy increases with increasing strain rate and deformation temperature decreasing, which is characterized by work-hardening, dynamic recovery, dynamic recrystallization. The effects of strain rate and temperature on hot deformation behavior were represented by Zener–Hollomon parameter including Arrhenius term. The power law, exponential, and sin hyperbolic types of Zener–Hollomon equations were used to determine the hot deformation behavior of Al-Cu-Mg-Pb alloy. The results suggested that the highest correlation coefficient was achieved for the hyperbolic sine law for the studied material. So the proposed deformation constitutive equations can be used for numerical simulation of hot forming processes and for choosing proper forming parameters in engineering practice accurately.